Liga Hanseatica. Eine Analyse aus linguistischer und kulturwissenschaftlicher Sicht - Lyubov Nefedova (Linguistische Treffen in Wrocław, 2021)
The article is devoted to research into the Hanse concept from a linguistic and cultural view and is therefore an addition to the current studies in the field of culturally oriented German linguistics. The focus of this work is a corpus-based analysis of the use of the lexeme Hanse and other culturally bound lexemes (Realia), such as Hanseatic City, Hanseatic, Hansetag, Hanse Sail and others, which represent the Hanse concept in the current discourse and provide an insight into its сonceptual content. It was found that the lexemes Hanse, Hansetag, Hanseatic City represent a cultural concept whose important semantic / conceptual features are community, trade alliance of merchants (of cities) and the past (middle ages). The old Hanseatic League is an association of merchants, and later of trading cities in the Middle Ages, formed to represent common, above all economic interests. It is also called Deutsche Hanse, Latin Hansa Teutonica or Hansa Alemanniae and is considered a unique phenomenon in German history. The Hanseatic League of the Modern Era, founded in 1980 (the city union DIE HANSE), which comprises 16 countries, is a new kind of community, a living and cultural community of cities across borders. It is an alliance of European cities in a common multicultural area with the aim of making a contribution to the economic, cultural, social and national unification of Europe. Today the alliance includes 195 cities in Central, Northern and Northeastern Europe, including cities outside the German-speaking area. The Lexem Hanse is embedded in new contexts in contemporary discourse, it appears with adjectives used attributively such as new and international: The New Hanse, the International Hanseatic Day. The lexem Hanseatic City is part of the name of numerous European cities that used to belong to the Hanseatic League. The new Hanse term consequently contains the semantic / conceptual characteristic international. From this it can be concluded that the mono-cultural Hanse concept (German Hanse) has developed over time into a transcultural, as well as a multi- and intercultural integration concept (international Hanse) that connects different cultures.